ENVIRONMENTAL ETHICS IN THE THOUGHT OF SAID NURSI: RELEVANCE TO THE ECOLOGICAL CRISIS IN SOUTH KALIMANTAN - Izhar Muttakin; Norhidayat; Ahmad Mujahid (As-Sulthan Journal of Education, 2026)
The climate crisis in South Kalimantan represents not only an ecological breakdown but also a profound spiritual crisis caused by the loss of tawhidic consciousness in modern humanity. This study explores the relevance of Bediuzzaman Said Nursi’s thought to Islamic environmental ethics in the context of South Kalimantan’s ecological crisis. Using a theological-ecological approach through content analysis of Risale-i Nur and empirical data from BMKG, WALHI, and the Provincial Environmental Agency (DLH), this research demonstrates that Nursi’s ideas provide a conceptual foundation for an eco-spiritual ethics paradigm grounded in ecological tawhid, the trust of khalifah, and ukhuwah makhlukiyah (universal kinship of beings). From a Sufi perspective, nature is viewed as the Book of God (kitâbullâh), reflecting the Divine Names and functioning as a cosmic dhikr of creation. Hence, ecological degradation is understood as a manifestation of humanity’s spiritual failure to maintain divine balance. By integrating Sufi spirituality with Banjar local wisdom, this article expands the horizon of Islamic ecotheology from its Middle Eastern center toward a transformative and sustainable tropical Southeast Asian perspective.